HUBUNGAN ANTARA KESEPIAN DAN OBESITAS: META-ANALISIS STUDI OBSERVASIONAL - Tursina, Elsa; Hikmah, Annisa Arifatul; Fatony, Riska Fajar; Yusuf, Muhammad (Jurnal Medicare, 2025)
Loneliness has been increasingly recognized as a psychosocial factor influencing obesity risk. However, findings from individual studies remain inconsistent. This meta-analysis aimed to analyze and estimate the pooled association between loneliness and obesity. A meta-analysis study using the PICO framework, adults (population), loneliness (intervention), not lonely (comparison), and obesity (Outcome). A search was conducted in PubMed, ScienceDirect, and Scopus databases for studies published between 2015 and 2025 following PRISMA guidelines. Search terms used were: ("loneliness" OR "social isolation") AND ("obesity" OR "BMI" OR "overweight") AND ("cross-sectional" OR "observational"). The inclusion criteria of the studies included were cross-sectional, reported odds ratios (OR) or adjusted odds ratios (AOR) with 95% confidence intervals (CI), and involved adult populations. Data were synthesized and analyzed using RevMan 5.3. Four studies (n = 137,846) met the inclusion criteria from Europe and South America. The pooled analysis showed individuals who experienced loneliness had 1.39 times the risk of obesity compared to those who did not feel lonely (AOR = 1.39; 95% CI= 1.09 to 1.76; p = 0.007). In conclusion, individuals who experienced loneliness had the risk of obesity compared to those who did not feel lonely.